HARDLY VISIBLE, HIGHLY ADMIRED? YOUTH PERCEPTIONS OF THE EU IN KAZAKHSTAN - Arynov, Zhanibek (Journal of Eurasian Studies, 2021)
Youth have always been one of the central target audiences of the European Union’s (EU) policies towards Central Asia, which was once again emphasised in the recent EU Strategy for the region. This paper scrutinises how youth repre sentatives in Kazakhstan, Brussels’ closest partner in the region, perceive the EU and its policies. By doing so, the paper shifts the focus from the EU-centric assessment of its external activities, which has long dominated the academic literature, and provides a ‘voice’ to the targets of the EU’s various initiatives. Examining data obtained through the method of pictorial test and focus group discussions with students of leading Kazakhstani universities, the paper argues that the issue Brussels faces among youth is not an image problem, rather it is a visibility issue. Although Kazakhstani youth are aware of the EU’s main ‘attributes’ at the basic level, they have little knowledge that goes beyond stereotypical, yet positive, images of it. This stereotyped admiration towards the EU, however, is not necessarily an outcome of Brussels’ successful policies, rather it is partly inherited from the historically idealised image of Europe. The paper suggests that increasing its visibility and better communicating its policies and messages need to be a priority for the EU in Central Asia
Keywords: Type of access: Open Access; European Union; Kazakhstan; perception; image; youth; visibility